Spiritual Needs and Resilience Women with Cervical Cancer - Supatmi, Supatmi; Yumni, Fathiya Lutfil; Reliani, Reliani; Priyantini, Diah (Babali Nursing Research, 2025)
Introduction: Spiritual needs are crucial in providing support for cervical cancer patients in palliative care. Spiritual support helps reduce feelings of despair and depression, enabling patients to undergo treatment and maintain their quality of life. Resilience refers to individual characteristics that are adaptable and support successful coping with cancer. This study aimed to examine the spiritual needs and resilience of women with cervical cancer. Method: This research employed a correlational analytical design with a cross-sectional approach conducted in North Surabaya, which has the highest number of cervical cancer patients in the city of Surabaya. All women with cervical cancer recorded in the integrated service system constituted the population, and 42 women were recruited using total sampling. Spiritual needs were assessed using the Spiritual Needs Questionnaire, while resilience was measured with the Connor-Davidson Resilience Scale (CD-RISC). The collected data were analyzed using the Spearman rho test with a 95% confidence interval and an alpha (α) of 0.05. Results: A significant relationship was found between spiritual needs and resilience in women with cervical cancer (p = 0.000), with a correlation coefficient of r = 0.572, indicating a strong relationship. Conclusion: A spiritual approach is essential for cervical cancer patients to enhance their spiritual well-being, thereby fostering physical and psychosocial resilience.